KAJIAN ANALISIS POTENSI ENERGI BARU TERBARUKAN PADA KOTA SAMARINDA TAHUN 2023-2024 DALAM MENDUKUNG BAURAN ENERGI LISTRIK NASIONAL - Larasati, Tantra Diwa; Alham, Nur Rani; Utomo, Restu Mukti (Universitas Mulawarman, 2024)
The use of new and renewable energy is currently still relatively small, it’s 13.09% compared to fossil energy which is still the national primary energy. The government itself has set a target for renewable energy utilization to reach at least 31% by 2050, and the city of Samarinda is part of East Kalimantan province, which is the largest coal and oil and gas producer in Indonesia. To assist the government in achieving the EBT’s target, an analysis study was carried out on the EBT Potential in the city of Samarinda. This research was carried out by collecting data both by obtaining data in documents and taking direct measurements at certain locations. From this research, we obtained the results of identifying the type of EBT and the potential for electrical energy, namely Waste Energy, of 881.49 MW/Year. Then Solar Energy is 1,191 MWh. Wind energy is 9,933 Kwh and Water Energy for Microhydro Power Plant calculations is 292.33 Kw per year.. Keywords: potency, EBT, Energy